2015
DOI: 10.1155/2015/962891
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes after Binocular Implantation of a New Trifocal Diffractive Intraocular Lens

Abstract: Purpose. To evaluate visual, refractive, and contrast sensitivity outcomes, as well as the incidence of pseudophakic photic phenomena and patient satisfaction after bilateral diffractive trifocal intraocular lens (IOL) implantation. Methods. This prospective nonrandomized study included consecutive patients undergoing cataract surgery with bilateral implantation of a diffractive trifocal IOL (AT LISA tri 839MP, Carl Zeiss Meditec). Distance, intermediate, and near visual outcomes were evaluated as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 15 publications
(45 reference statements)
5
16
0
2
Order By: Relevance
“…Likewise, Vryghem and Heireman [28] and Kretz et al [31] also achieved the highest level of contrast sensitivity at 3 cpd. In the studies conducted by Mojzis et al [22] and Sheppard et al [25], the contrast sensitivity curve revealed that the patients had high sensitivity to medium (6 cpd) spatial frequencies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Likewise, Vryghem and Heireman [28] and Kretz et al [31] also achieved the highest level of contrast sensitivity at 3 cpd. In the studies conducted by Mojzis et al [22] and Sheppard et al [25], the contrast sensitivity curve revealed that the patients had high sensitivity to medium (6 cpd) spatial frequencies.…”
Section: Discussionmentioning
confidence: 92%
“…They also reported that the mean binocular UDVA, UIVA, and UNVA were 0.01 ± 0.11 logMAR, 0.32 ± 0.15 logMAR, and 0.15 ± 0.13 logMAR, respectively, in the patients implanted with trifocal IOL (30 eyes of 15 patients) at the postoperative 6th month. Kretz et al [31] reported a binocular UDVA of 0.00 logMAR or better and a binocular UIVA of 0.10 logMAR or better in all patients undergoing AT LISA trifocal IOL implantation (76 eyes of 38 patients), and a binocular UNVA of 0.10 logMAR or better in 85% of the patients at the postoperative 3 months. Mojzis et al [32] conducted a study in the patients (120 eyes of 60 patients) who underwent cataract surgery with trifocal AT LISA IOL implantation; and followed the patients for a postoperative period of 12- month.…”
Section: Discussionmentioning
confidence: 99%
“…Einleitung Die trifokale diffraktive IOL-Technologie hat sich in der Kataraktchirurgie und beim refraktiven Linsenaustausch als effektive Methode herausgestellt, das Sehvermögen über einen weiten Entfernungsbereich wiederherzustellen [1][2][3][4][5][6][7][8][9][10][11]. Das spezielle Linsendesign verteilt das eintreffende Licht auf 3 Brennpunkte und ermöglicht den Patienten ein funktionelles Sehvermögen mit minimalen Lichtphänomenen in Ferne, Intermediärbereich und Nähe [1][2][3][4][5][6][7][8][9][10][11]. Bei Patienten mit signifikantem Hornhautastigmatismus ist der Nutzen einer sphärischen trifokalen Linse begrenzt, da meist keine Brillenfreiheit über mehrere Distanzen erreicht wird.…”
Section: Clinical Comparison Of a Trifocal And A Trifocal-toric Intraunclassified
“…A c c e p t e d M a n u s c r i p t 3 corneal spherical aberration, 4,5 regular corneal astigmatism, 6,7 corneal irregular astigmatism, 8,9 and effective lens addition. [10][11][12] The literature is full of studies reporting results with several MIOLs according to the standards, [13][14][15][16][17][18][19][20][21][22][23][24] but it is still not clear the influence of biometric factors on the performance of each particular IOL according to the characteristics of the patient. The main aim of this study was to evaluate the performance of a high addition MIOL by means of computing the area under the visual acuity defocus curve 25 and correlate it with several biometric parameters.…”
mentioning
confidence: 99%